AGAINST RELIGIOUS FORMALISM: The Dynamics of Young Urban Sufism in Yogyakarta (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
This article discusses two elements of the evolution of Sufism amongst young urbanites. First, it explores the dynamics of the youths who are actively involved in spiritual activities at cafés, councils, and pesantren in Yogyakarta. Second, it investigates their response to the religious formalism promoted by Salafist organizations. Such spirituality offers a means of enriching religious perspectives and discourses. At the same time, urban Sufism (as promoted by zikir groups, prayer groups, and pesantren) has been challenged by Islamic organizations that adhere to doctrines of Salafism/Wahhabism and transnational Islamism. This study employs a qualitative approach by collecting its data through observations and interviews with urban Sufis in Yogyakarta, Indonesia. It finds that youths' opposition is not only to religious formalism produced by Salafists but also to formality and exclusivity known as brotherhoodism or tariqa (Sufi order) from Sufi itself. Their strict opposition to the dualism of religious formality provides them with an important means of critiquing the dominant strains of tasawwuf and religious schools (tariqa) while offering new religious dynamics.